Microbiota and Cancer: The Emerging Beneficial Role of Bifidobacteria in Cancer Immunotherapy - Longhi, Giulia; van Sinderen, Douwe; Ventura, Marco; Turroni, Francesca (Frontiers in Microbiology, 2020)
Many intestinal bacteria are believed to be involved in various inflammatory and immune processes that influence tumor etiology because of their metabolic properties and their ability to alter the microbiota homeostasis. Although many functions of the microbiota are still unclear, there is compelling experimental evidence showing that the intestinal microbiota is able to modulate carcinogenesis and the response to anticancer therapies, both in the intestinal tract and other body sites. Among the wide variety of gut-colonizing microorganisms, various species belonging to the Bifidobacterium genus are believed to elicit beneficial effects on human physiology and on the host-immune system. Recent findings, based on preclinical mouse models and on human clinical trials, have demonstrated the impact of gut commensals including bifidobacteria on the efficacy of tumour-targeting immunotherapy. Although the underlying molecular mechanisms remain obscure, bifidobacteria and other microorganisms have become a promising aid to immunotherapeutic procedures that are currently applied to treat cancer. The present review focuses on strategies to recruit the microbiome in order to enhance anticancer responses and develop therapies aimed at fighting the onset and progression of malignancies.